Shedding Light on Anesthetic Mechanisms: Application of Photoaffinity Ligands. (November 2016) - Woll, Kellie A.; Dailey, William P.; Brannigan, Grace; Eckenhoff, Roderic G.
Abstract : Anesthetic photoaffinity ligands have had an increasing presence within anesthesiology research. These ligands mimic parent general anesthetics and allow investigators to study anesthetic interactions with receptors and enzymes; identify novel targets; and determine distribution within biological systems. To date, nearly all general anesthetics used in medicine have a corresponding photoaffinity ligand represented in the literature. In this review, we examine all aspects of the current methodologies, including ligand design, characterization, and deployment. Finally we offer points of consideration and highlight the future outlook as more photoaffinity ligands emerge within the field. Abstract : Published ahead of print July 26, 2016.